PMMA (polymethyl methacrylate) glue with high ionic conductivity and preparation method thereof

By preparing the PMMA emulsion of hard-core soft shells, combined with modified β-potassium cylindrical and thickener, combined with the complexing reaction of lithium nitrate and propyl 3-sulfonate potassium salt of methacrylate, the preparation problem of high ionic conductivity PMMA glue is solved, and the glue with high mechanical properties and high ionic conductivity is achieved, meeting the needs of lithium-ion battery separator adhesives.

CN119775930APending Publication Date: 2025-04-08CYG NEW ENERGY MATERIAL RESEARCH INSTITUTE (GUANGDONG) CO LTD

Patent Information

Application Number
CN202411985637.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

There is a lack of a high ionic conductivity PMMA glue on the market for simple preparation, low cost and good mechanical properties after curing, especially in the application of lithium-ion battery separator adhesives.

Method used

By preparing a hard-core soft shell PMMA emulsion and combining with modified β-potassium cylindrite and thickener, combined with complexing reaction of lithium nitrate and propyl 3-sulfonate potassium salt of methacrylate, PMMA glue with high ionic conductivity and good mechanical properties was prepared.

Benefits of technology

The high mechanical properties and high ionic conductivity of the PMMA glue after curing are achieved, which meets the needs of lithium-ion battery separator adhesives, and the preparation method is simple and low cost.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the field of PMMA emulsion, in particular to high-ionic-conductivity PMMA glue and a preparation method thereof.The high-ionic-conductivity PMMA glue is prepared from, by weight, 80-90 parts of PMMA emulsion, 2-3 parts of modified beta-kaliophilite and 1-3 parts of thickening agent. The PMMA glue with high ionic conductivity prepared by the invention has the characteristics of good mechanical property after curing, simple preparation method and low cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of adhesives, and in particular to a PMMA glue with high ionic conductivity and a preparation method thereof. Background Art

[0002] Lithium-ion battery is a highly efficient rechargeable battery that charges and discharges by the movement of lithium ions between the positive and negative electrodes. This type of battery has the advantages of high energy density, high voltage, wide operating temperature range, and long storage life. It is widely used in mobile phones, laptops, electric vehicles, energy storage systems and other fields. The diaphragm is an important component in the battery. Its main function is to isolate the electrolyte between the positive and negative electrodes and prevent direct contact, thereby avoiding dangerous situations such as overheating, fire or explosion of the battery. In addition, the battery diaphragm can also protect the battery cell from mechanical shock and damage. The diaphragm needs to fit tightly to the negative electrode of the battery to prevent the electrolyte from leaking or penetrating into the diaphragm and affecting the performance and life of the battery. Therefore, it is often necessary to apply a layer of glue on the diaphragm. Battery diaphragm adhesives not only need to have good high temperature resistance, good chemical resistance, good aging resistance, strong viscosity, etc., but also need to have high ionic conductivity.

[0003] Patent CN111211277B discloses a method for preparing a PMMA gel-coated diaphragm, comprising the following steps: (1) mixing PMMA powder with water, adding a grafting agent, grinding, and then stirring and dispersing to obtain a grafted PMMA dispersion; (2) diluting the grafted PMMA dispersion to prepare a coating slurry; (3) feeding the diaphragm into a coating device and coating it with the coating slurry; (4) drying and rolling up the coated diaphragm to obtain a PMMA gel-coated diaphragm. This invention greatly improves the grafting rate of the grafting agent on the PMMA surface through a high-solid content grinding grafting method, thereby improving the uniformity and stability of the PMMA slurry, and further improving the coating quality. The prepared coated diaphragm has high ionic conductivity and excellent bonding properties. However, the preparation method of this grafted PMMA dispersion is relatively delicate, which is not conducive to industrial production, and PMMA has poor mechanical properties when used alone.

[0004] Patent CN115347325B discloses a composite diaphragm and its preparation method and sodium ion battery, wherein the composite diaphragm comprises a base film and a mixed polymer coating coated on at least one side of the base film; the mixed polymer coating comprises polydopamine and polymethyl methacrylate; the slurry of the mixed polymer coating comprises the following components: polydopamine emulsion, polymethyl methacrylate, binder, dispersant, thickener and wetting agent. The mixed polymer coating used in the composite diaphragm provided by the invention has good interface bonding performance and heat resistance, and good wettability to electrolyte, but the cost of polydopamine emulsion is relatively high.

[0005] Therefore, the market is in urgent need of a high ionic conductivity PMMA glue with simple preparation method, low cost and good mechanical properties after curing. Summary of the invention

[0006] In view of the problems existing in the prior art, the purpose of the present invention is to obtain a PMMA glue with high ionic conductivity, which has a simple preparation method, low cost and good mechanical properties after curing.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0008] The first aspect of the present invention provides a PMMA glue with high ionic conductivity, which comprises the following raw materials, by weight: 80-90 parts of PMMA emulsion, 2-3 parts of modified β-potassium pyroxene, and 1-3 parts of thickener.

[0009] The present application prepares a hard-core soft-shell PMMA emulsion and then compounding it with modified β-potassium pyroxene and a thickener to obtain a high ionic conductivity PMMA glue with good mechanical properties after curing.

[0010] In some embodiments, the method for preparing the PMMA emulsion comprises the following steps:

[0011] A1. Add dispersant and ethanol into deionized water, stir at room temperature until dissolved, add part of monomer mixture A and azobisisobutyronitrile, stir for 20-30 minutes, heat to 70-80°C and react for 12-16 minutes, add the remaining amount of monomer mixture A and azobisisobutyronitrile dropwise and react for 2-3 hours to obtain a core layer emulsion;

[0012] A2, adding monomer mixture B, sodium dodecyl sulfonate, epoxy resin and ethanol into deionized water, stirring at 750-850 rpm and room temperature for 20-30 min to obtain a shell emulsion;

[0013] A3. Add the shell layer emulsion obtained in step A2 and 1-3 wt % sodium persulfate aqueous solution dropwise to the core layer emulsion obtained in step A1 at 70-80° C., and react for 3-5 hours to obtain a PMMA emulsion.

[0014] In some embodiments, the method for preparing the monomer mixed solution A comprises the following steps:

[0015] B1. Add cerium nitrate to a 15-17 wt % sodium phosphate aqueous solution, and stir at 40-60° C. for 40-60 min to obtain a phosphate metal ion complex solution;

[0016] B2, adding lithium nitrate, citric acid and potassium salt of 3-sulfonyl methacrylate to the phosphate metal ion complex solution obtained in step B1, adjusting the pH to 8-12, reacting at 70-90° C. for 40-60 min, obtaining a liquid through aging, crystallization, precipitation and solid-liquid separation, and drying the liquid to obtain a modified monomer;

[0017] B3. Add the modified monomer obtained in step B2, styrene, methyl methacrylate, N-vinyl formamide and hydroxyethyl methacrylate into a reaction vessel and stir at 30-40° C. for 20-30 min to obtain a monomer mixture A.

[0018] Preferably, the mass ratio of the 15-17 wt % sodium phosphate aqueous solution to cerium nitrate is 1:(0.2-0.4).

[0019] In the prior art, in order to further improve the ionic conductivity of the PMMA glue layer, it is often necessary to add lithium salt as a carrier for lithium ion transmission. However, the lithium salt can only float on the surface of the PMMA glue layer and has little effect on the lithium ion conductivity inside it. The present application adds lithium nitrate and potassium 3-sulfonyl methacrylate to a phosphate metal ion complex solution complexed with cerium ions so that the potassium ions in the system preferentially combine with phosphate to form a potassium phosphate precipitate with poor solubility, and then separates the lithium 3-sulfonyl methacrylate and the cerium salt. The PMMA glue prepared by using the above-mentioned salts can introduce lithium ions into the PMMA chain segments, thereby further improving the lithium ion conductivity of the PMMA glue layer.

[0020] In some embodiments, the mass ratio of the potassium salt of 3-sulfonate propyl methacrylate to lithium nitrate is (3-5):1.

[0021] When there are more potassium ions in the system, they cannot be completely complexed by phosphate ions, which will cause the sulfonate on 3-sulfonyl methacrylate to have a poor complexing effect on lithium ions and cerium. The present application limits the mass ratio of 3-sulfonyl methacrylate potassium salt and lithium nitrate, which is beneficial to improving the yield and purity of 3-sulfonyl methacrylate lithium salt and cerium salt, thereby improving the ionic conductivity of PMMA glue.

[0022] In some embodiments, the mass ratio of the modified monomer, styrene, methyl methacrylate, N-vinyl formamide, and hydroxyethyl methacrylate is (0.3-0.5):1:(2-3):(0.1-0.2):(0.1-0.2).

[0023] The modified monomer is grafted onto the PMMA core layer, which makes the core layer charged, and may affect the grafting reaction of the shell material, reduce the stability of the emulsion and cause the mechanical properties of the PMMA glue layer to decrease. The present application can improve the ionic conductivity of the PMMA glue while ensuring the stability of the PMMA core-shell emulsion by limiting the ratio of the modified monomer to each monomer.

[0024] In some embodiments, the preparation method of the monomer mixture B comprises the following steps: adding 2-hydroxyethyl acrylate, 2-carboxyethyl acrylate, and ethylene glycol dimethacrylate into a reaction container and stirring at 30-40° C. for 20-30 minutes, wherein the mass ratio of the three is 1: (0.03-0.05): (0.2-0.3).

[0025] In some embodiments, the preparation method of the modified β-potassium pyroxene comprises the following steps: adding β-potassium pyroxene and bis(dioctyl pyrophosphate)ethylene titanate to 89-95wt% ethanol, stirring at room temperature for 20-30 minutes, ball milling at a speed of 500-700 rpm for 2-3 hours, and spray drying to obtain modified β-potassium pyroxene.

[0026] In the present application, β-eucryptite and bis(dioctyl pyrophosphate)ethylene titanate are added to ethanol and then ball-milled. On the one hand, this can reduce the particle size of the β-eucryptite and increase the porosity of the PMMA adhesive layer. On the other hand, it can make the materials evenly dispersed, which is beneficial to the subsequent spray-drying to obtain the modified β-eucryptite to be evenly coated with bis(dioctyl pyrophosphate)ethylene titanate, which is beneficial to improve its compatibility with PMMA and thus improve the mechanical properties of the PMMA adhesive layer, and at the same time, the PMMA adhesive layer can have an extremely small shrinkage rate; in addition, the crystal structure of β-eucryptite contains both octahedral voids and tetrahedral voids. When the battery generates heat during the charging and discharging process, the temperature becomes higher, causing the octahedral voids to become larger, and the lithium ions in the crystal will gradually move, thereby promoting the migration of lithium ions inside the PMMA adhesive layer, compensating for the loss of lithium ions in the electrochemical reaction, and helping to improve the lithium ion conductivity of the PMMA adhesive layer. The multiple phosphoacyloxy groups on bis(dioctylpyrophosphate)ethylene titanate can generate hydrogen bonds and ionic bonds with the sulfonic acid groups, making it easy to form a lithium ion migration path between the modified β-eucryptite and the modified PMMA, which is beneficial to improving the lithium ion conductivity of the PMMA glue layer.

[0027] In some embodiments, the mass ratio of the β-potassium nepheline, bis(dioctyl pyrophosphate)ethylene titanate and 89-95 wt % of ethanol is (0.2-0.3):(0.1-0.2):1.

[0028] The residual bis(dioctyl pyrophosphate)ethylene titanate that does not play a coupling role may load lithium ions and affect the transfer of lithium ions. The present application reduces the residual bis(dioctyl pyrophosphate)ethylene titanate that does not play a coupling role by limiting the ratio of β-potassium nepheline, bis(dioctyl pyrophosphate)ethylene titanate and 89-95wt% of ethanol, which is beneficial to improving the lithium ion conductivity of the PMMA adhesive layer.

[0029] In some embodiments, the thickener is sodium carboxymethyl cellulose or sodium polyacrylate.

[0030] On the other hand, the present invention provides a method for preparing PMMA glue with high ionic conductivity, comprising the following steps: adding modified β-potassium pyroxene and a thickener into a PMMA emulsion and mixing at room temperature for 40-60 minutes to obtain the glue.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] (1) The present invention prepares a hard-core soft-shell PMMA emulsion and then compounding it with modified β-potassium pyroxene and a thickener to obtain a high ionic conductivity PMMA glue with good mechanical properties after curing.

[0033] (2) The present invention adds lithium nitrate and potassium 3-sulfonyl methacrylate to a phosphate metal ion complex solution complexed with cerium ions so that the potassium ions in the system preferentially combine with phosphate to form a potassium phosphate precipitate with poor solubility, and then separates the lithium 3-sulfonyl methacrylate and the cerium salt. The PMMA glue prepared by the above methods can introduce lithium ions into the PMMA chain segments, thereby further improving the lithium ion conductivity of the PMMA glue layer.

[0034] (3) The present invention adds β-eucryptite and bis(dioctyl pyrophosphate)ethylene titanate to ethanol and then ball-mills the mixture. On the one hand, this helps to improve the compatibility of β-eucryptite with PMMA and thus improve the mechanical properties of the PMMA adhesive layer, while also allowing the PMMA adhesive layer to have an extremely small shrinkage rate. In addition, the lithium ions in the β-eucryptite will move during the charge and discharge process of the battery, which helps to improve the lithium ion conductivity of the PMMA adhesive layer. In addition, the multiple phosphate groups on the bis(dioctyl pyrophosphate)ethylene titanate can generate hydrogen bonds and ionic bonds with the sulfonic acid groups, making it easy to form a lithium ion movement path between the modified β-eucryptite and the modified PMMA, which helps to improve the lithium ion conductivity of the PMMA adhesive layer. DETAILED DESCRIPTION

[0035] The present invention will be described below in conjunction with specific embodiments. It should be noted that the following embodiments are examples of the present invention and are only used to illustrate the present invention, but not to limit the present invention. Other combinations and various modifications within the concept of the present invention may be performed without departing from the spirit or scope of the present invention.

[0036] In the following embodiments and comparative examples, except for modified β-potassium pyroxene and PMMA emulsion, the other compounds and related reagents used can be purchased from the market. Among them, the average particle size of β-potassium pyroxene is 120 mesh, purchased from Zibo Chendong New Materials Co., Ltd.; the viscosity of sodium carboxymethyl cellulose at 25°C is 2320mPa.s, purchased from Jiashan Sanyi New Materials Co., Ltd.; the model of epoxy resin is WL90, purchased from Nanjing Xinyi Synthesis Technology Co., Ltd.; the model of polyvinyl pyrrolidone is K30, purchased from Huzhou Shenhua Polymer Materials Co., Ltd.

[0037] Preparation Example 1

[0038] The method for preparing the monomer mixed solution A-1 comprises the following steps:

[0039] B1. Add 3 g of cerium nitrate to 10 g of 16 wt% sodium phosphate aqueous solution, and stir at 50° C. for 50 min to obtain a phosphate metal ion complex solution;

[0040] B2, adding 1g of lithium nitrate, 0.1g of citric acid and 4g of potassium salt of 3-sulfonyl methacrylate to 12g of the phosphate metal ion complex solution obtained in step A1, adding sodium hydroxide to adjust the pH to 10, reacting at 80°C for 50min, obtaining a liquid through aging, crystallization, precipitation and solid-liquid separation, and drying the liquid to obtain a modified monomer;

[0041] B3. Add 4 g of the modified monomer obtained in step B2, 10 g of styrene, 25 g of methyl methacrylate, 1.5 g of N-vinylformamide, and 1.5 g of hydroxyethyl methacrylate into a reaction vessel and stir at 35° C. for 25 min to obtain a monomer mixture A-1.

[0042] Preparation Example 2

[0043] The preparation method of the monomer mixture A-2 is the same as that of Preparation Example 1, except that the addition amount of 3-sulfonic acid propyl methacrylate potassium salt is 2 g.

[0044] Preparation Example 3

[0045] The preparation method of monomer mixed solution A-3 is the same as that of Preparation Example 1, except that the amount of modified monomer added is 7 g.

[0046] Preparation Example 4

[0047] The preparation method of monomer mixture A-4 comprises the following steps: adding 10 g styrene, 25 g methyl methacrylate, 1.5 g N-vinyl formamide, and 1.5 g hydroxyethyl methacrylate into a reaction container and stirring at 35° C. for 25 min to obtain monomer mixture A-4.

[0048] Preparation Example 5

[0049] The preparation method of the monomer mixed solution B-1 comprises the following steps: adding 10 g of 2-hydroxyethyl acrylate, 0.4 g of 2-carboxyethyl acrylate and 2.5 g of ethylene glycol dimethacrylate into a reaction container and stirring at 35° C. for 25 min to obtain the obtained product.

[0050] Preparation Example 6

[0051] The preparation method of PMMA emulsion-1 comprises the following steps:

[0052] A1. Add 10g polyvinyl pyrrolidone and 10g anhydrous ethanol into 10g deionized water, stir at room temperature until dissolved, add 15g monomer mixture A-1 and 1g azobisisobutyronitrile and stir for 25min, heat to 75℃ and react for 14min, add dropwise 25g monomer mixture A-1 and 1g azobisisobutyronitrile and react for 2.5h, with a dropping speed of 1g / min, to obtain a core layer emulsion;

[0053] A2, adding 12g of monomer mixture B, 1g of sodium dodecyl sulfate, 1g of epoxy resin, and 10g of anhydrous ethanol to 10g of deionized water, stirring at 800rpm and room temperature for 25min to obtain a shell emulsion;

[0054] A3. Add 10 g of the shell layer emulsion obtained in step A2 and 1 g of a 2 wt% sodium persulfate aqueous solution to the core layer emulsion obtained in step A1 at 75° C. and react for 4 hours to obtain PMMA emulsion-1.

[0055] Preparation Example 7

[0056] The preparation method of PMMA emulsion-2 is the same as that of Preparation Example 6, except that an equal amount of monomer mixture A-1 is replaced by monomer mixture A-2.

[0057] Preparation Example 8

[0058] The preparation method of PMMA emulsion-3 is the same as that of Preparation Example 6, except that an equal amount of monomer mixture A-1 is replaced by monomer mixture A-3.

[0059] Preparation Example 8

[0060] The preparation method of PMMA emulsion-4 is the same as that of Preparation Example 6, except that an equal amount of monomer mixture A-1 is replaced by monomer mixture A-4.

[0061] Preparation Example 9

[0062] The preparation method of modified β-potassium pyroxene-1 comprises the following steps: adding 2.5 g of β-potassium pyroxene and 1.5 g of bis(dioctyl pyrophosphate acyloxy)ethylene titanate into 10 g of 92 wt% ethanol, stirring at room temperature for 25 min, ball milling at a rotation speed of 600 rpm for 2.5 h, and spray drying to obtain modified β-potassium pyroxene-1.

[0063] Preparation Example 10

[0064] The preparation method of modified β-potassium pyroxene-2 ​​is the same as that of Preparation Example 9, except that the addition amount of β-potassium pyroxene is 1.5 g.

[0065] Preparation Example 11

[0066] The preparation method of modified β-potassium pyroxene-3 is the same as that of Preparation Example 9, except that the addition amount of bis(dioctyl pyrophosphate)ethylene titanate is 2.5 g.

[0067] Example 1

[0068] A PMMA glue with high ionic conductivity comprises the following raw materials, measured by weight: 85 parts of PMMA emulsion-1, 2.5 parts of modified β-potassium pyroxene-1, and 2 parts of sodium carboxymethyl cellulose.

[0069] The method for preparing PMMA glue with high ionic conductivity in this embodiment comprises the following steps: adding modified β-potassium pyroxene-1 and sodium carboxymethyl cellulose to PMMA emulsion-1 and mixing at room temperature for 50 minutes to obtain the glue.

[0070] Example 2

[0071] A PMMA glue with high ionic conductivity comprises the following raw materials, measured by weight: 80 parts of PMMA emulsion-1, 2 parts of modified β-potassium pyroxene-1, and 1 part of sodium carboxymethyl cellulose.

[0072] The method for preparing PMMA glue with high ionic conductivity in this embodiment comprises the following steps: adding modified β-potassium pyroxene-1 and sodium carboxymethyl cellulose to PMMA emulsion-1 and mixing at room temperature for 40 minutes to obtain the glue.

[0073] Example 3

[0074] A PMMA glue with high ionic conductivity comprises the following raw materials, measured by weight: 90 parts of PMMA emulsion-1, 3 parts of modified β-potassium pyroxene-1, and 3 parts of sodium carboxymethyl cellulose.

[0075] The method for preparing PMMA glue with high ionic conductivity in this embodiment comprises the following steps: adding modified β-potassium pyroxene-1 and sodium carboxymethyl cellulose to PMMA emulsion-1 and mixing at room temperature for 60 minutes to obtain the glue.

[0076] Example 4

[0077] A PMMA glue with high ionic conductivity and a preparation method thereof. The specific implementation manner is the same as that of Example 1, except that an equal amount of PMMA emulsion-1 is replaced by PMMA emulsion-2.

[0078] Example 5

[0079] A PMMA glue with high ionic conductivity and a preparation method thereof. The specific implementation manner is the same as that of Example 1, except that an equal amount of PMMA emulsion-1 is replaced by PMMA emulsion-3.

[0080] Example 6

[0081] A PMMA glue with high ionic conductivity and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that an equal amount of modified β-potassium pyroxene-1 is replaced by modified β-potassium pyroxene-2.

[0082] Example 7

[0083] A PMMA glue with high ionic conductivity and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that an equal amount of modified β-potassium pyroxene-1 is replaced by modified β-potassium pyroxene-3.

[0084] Example 8

[0085] A PMMA glue with high ionic conductivity and a preparation method thereof. The specific implementation manner is the same as that of Example 1, except that an equal amount of PMMA emulsion-1 is replaced by PMMA emulsion-4.

[0086] Comparative Example 1

[0087] A PMMA glue with high ionic conductivity and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that an equal amount of modified β-potassium pyroxene-1 is replaced by β-potassium pyroxene.

[0088] Performance Testing

[0089] 1. Sample preparation

[0090] (1) 20 g of the high ionic conductivity PMMA glue obtained in the above embodiments and comparative examples was placed in a 10 cm×10 cm×5 mm polytetrafluoroethylene mold and dried to obtain each high ionic conductivity PMMA glue layer.

[0091] (2) The high ion conductivity PMMA glue obtained in the above embodiments and comparative examples was coated on a commercially available polyethylene film, the thickness of the polyethylene was 202 μm, the coating thickness was 2 μm, and each diaphragm was obtained after drying. Each diaphragm was used to prepare a 2032-type lithium-ion battery. The electrode and electrolyte composition of the battery were: positive electrode: LiCoO 2 , electrolyte: LiPF 6 / EC / DMC, negative electrode: graphite.

[0092] 2. Performance Testing

[0093] (1) Mechanical properties: The tensile strength of each high ionic conductivity PMMA adhesive layer was tested in accordance with GB / T 1039-1992.

[0094] (2) Ionic conductivity: The 2032-type lithium-ion batteries prepared using various diaphragms were subjected to EIS testing using an electrochemical workstation with a frequency range of 1200 kHz and an amplitude of 5 mV. The ionic conductivity of each diaphragm was calculated using the formula σ = L / (R × A), where L is the thickness of the diaphragm, A is the effective area of ​​the diaphragm, and R is the bulk resistance of the diaphragm. The resistance value at the intersection of the EIS curve and the real axis was taken.

[0095] Table 1

[0096] Group Tensile strength MPa Ionic conductivity mS / cm Example 1 4.55 3.827 Example 2 4.34 3.812 Example 3 4.47 3.787 Example 4 4.28 3.397 Example 5 3.89 3.721 Example 6 3.96 3.435 Example 7 4.25 3.572 Example 8 4.31 2.635 Comparative Example 1 3.62 2.823

[0097] It can be seen from the data in Table 1 that the PMMA glue in Examples 1-3 of the present invention has the advantages of good mechanical properties of the glue layer after curing and high ionic conductivity. From the comparison between Example 4 and Example 1, it can be seen that changing the ratio of potassium salt of 3-sulfonyl methacrylate and lithium nitrate will make the potassium ions unable to be completely complexed by phosphate ions, which will lead to the poor complexing effect of the sulfonate on 3-sulfonyl methacrylate on lithium ions and cerium, resulting in a decrease in the ionic conductivity of the PMMA glue; from the comparison between Example 5 and Example 1, it can be seen that changing the addition amount of the modified monomer will affect the grafting reaction of the shell material, reduce the stability of the emulsion, and cause the mechanical properties of the PMMA glue layer to decrease; from Examples 6 and 7, it can be seen that changing the addition amount of the modified monomer will affect the grafting reaction of the shell material, reduce the stability of the emulsion, and cause the mechanical properties of the PMMA glue layer to decrease. From the comparison with Example 1, it can be seen that changing the addition amount of β-potassium pyrophosphate or bis(dioctyl pyrophosphate)ethylene titanate will cause the bis(dioctyl pyrophosphate)ethylene titanate that does not play a coupling role to remain in the system, affecting the transfer of lithium ions, resulting in a decrease in the ionic conductivity of the PMMA glue, and will affect the dispersion effect of β-potassium pyrophosphate, resulting in a decrease in the mechanical properties of the PMMA glue layer; from the comparison between Example 8 and Example 1, it can be seen that the ionic conductivity of the PMMA glue that is not modified by the PMMA emulsion decreases; from the comparison between Comparative Example 1 and Example 1, it can be seen that without modifying the β-potassium pyrophosphate, the PMMA glue has poor mechanical properties of the glue layer after curing and low ionic conductivity.

[0098] The above implementation modes are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the content of the present invention and implement it, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A PMMA glue with high ionic conductivity, characterized in that: The following raw materials are included by weight: 80-90 parts of PMMA emulsion, 2-3 parts of modified β-potassium pyroxene and 1-3 parts of thickener.

2. The high ionic conductivity PMMA glue according to claim 1, characterized in that: The preparation method of the PMMA emulsion comprises the following steps: A1. Add dispersant and ethanol into deionized water, stir at room temperature until dissolved, add part of monomer mixture A and azobisisobutyronitrile, stir for 20-30 minutes, heat to 70-80°C and react for 12-16 minutes, add the remaining amount of monomer mixture A and azobisisobutyronitrile dropwise and react for 2-3 hours to obtain a core layer emulsion; A2, adding monomer mixture B, sodium dodecyl sulfonate, epoxy resin and ethanol into deionized water, stirring at 750-850 rpm and room temperature for 20-30 min to obtain a shell emulsion; A3. Add the shell layer emulsion obtained in step A2 and 1-3 wt % sodium persulfate aqueous solution dropwise to the core layer emulsion obtained in step A1 at 70-80° C., and react for 3-5 hours to obtain a PMMA emulsion.

3. The high ionic conductivity PMMA glue according to claim 2, characterized in that: The method for preparing the monomer mixed solution A comprises the following steps: B1. Add cerium nitrate to a 15-17 wt % sodium phosphate aqueous solution, and stir at 40-60° C. for 40-60 min to obtain a phosphate metal ion complex solution; B2, adding lithium nitrate, citric acid and potassium salt of 3-sulfonyl methacrylate to the phosphate metal ion complex solution obtained in step B1, adjusting the pH to 8-12, reacting at 70-90° C. for 40-60 min, obtaining a liquid through aging, crystallization, precipitation and solid-liquid separation, and drying the liquid to obtain a modified monomer; B3. Add the modified monomer obtained in step B2, styrene, methyl methacrylate, N-vinyl formamide and hydroxyethyl methacrylate into a reaction vessel and stir at 30-40° C. for 20-30 min to obtain a monomer mixture A.

4. The high ionic conductivity PMMA glue according to claim 3, characterized in that: The mass ratio of the potassium salt of 3-sulfonate propyl methacrylate to lithium nitrate is (3-5):

1.

5. The high ionic conductivity PMMA glue according to claim 3, characterized in that: The mass ratio of the modified monomer, styrene, methyl methacrylate, N-vinyl formamide and hydroxyethyl methacrylate is (0.3-0.5):1:(2-3):(0.1-0.2):(0.1-0.2).

6. The high ionic conductivity PMMA glue according to claim 2, characterized in that: The preparation method of the monomer mixed solution B comprises the following steps: adding 2-hydroxyethyl acrylate, 2-carboxyethyl acrylate and ethylene glycol dimethacrylate into a reaction container and stirring at 30-40° C. for 20-30 minutes, wherein the mass ratio of the three is 1: (0.03-0.05): (0.2-0.3).

7. The high ionic conductivity PMMA glue according to claim 1, characterized in that: The preparation method of the modified β-potassium pyroxene comprises the following steps: adding β-potassium pyroxene and bis(dioctyl pyrophosphate acyloxy)ethylene titanate into 89-95wt% ethanol, stirring at room temperature for 20-30min, ball milling at a speed of 500-700rpm for 2-3h, and spray drying to obtain the modified β-potassium pyroxene.

8. The high ionic conductivity PMMA glue according to claim 7, characterized in that: The mass ratio of the β-potassium pyroxene, bis(dioctyl pyrophosphate acyloxy)ethylene titanate and 89-95wt% of ethanol is (0.2-0.3):(0.1-0.2):

1.

9. The high ionic conductivity PMMA glue according to claim 1, characterized in that: The thickener is sodium carboxymethyl cellulose or sodium polyacrylate.

10. A method for preparing the PMMA glue with high ionic conductivity according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: adding modified beta-potassium pyroxene and a thickener into a PMMA emulsion and mixing them at room temperature for 40-60 minutes to obtain the product.

Citation Information

Patent Citations

  • A method for preparing a PMMA gel-coated diaphragm

    CN111211277B

  • Self-exhausting OCA optical adhesive as well as preparation method and application thereof

    CN112500816A

  • Room-temperature-cured reinforced PMMA (polymethyl methacrylate) adhesive and manufacturing method thereof

    CN116875232A

  • High-heat-resistance binder for lithium ion battery diaphragm and preparation method of high-heat-resistance binder

    CN118909570A

Cited By

  • PMMA glue with viscosity regulated and controlled by glacial acetic acid and preparation method of PMMA glue

    CN121950212A

  • Glue of PMMA with viscosity controlled by glacial acetic acid and preparation method thereof

    CN121950212B